Lamproderma echinosporum - Krivomaz, T. I.; Michaud, A.; Minter, D. W. (CABI, 2010)
Diagnostic features. Nivicolous species of Lamproderma have dark, often blackish, metallic, iridescent, shiny, separate, globose or nearly globose and stipitate to sessile sporocarps. Sporocarps of Lamproderma echinosporum are sessile or substipitate and on a narrow base. It may be distinguished from other similar nivicolous species of Lamproderma by its spore ornamentation, with large irregularly distributed spines.
Keywords: myxomycetes; міксоміцети; Lamproderma echinosporum